The effect of self- Learning on Tishreen University Classroom Teacher Student Employment of Synchronous and Asynchronous E-Voice Chatting Skills - Hosamo, Soha; Al-Abdullah, Fawaz (Jordan Journal of Educational Sciences, 2012)
The study aimed at measuring The effect of self- Learning on Tishreen University Classroom Teacher Student Employment of Synchronous and Asynchronous E-Voice Chatting Skills. The sample consisted of (22) students/ teachers from third year class room teachers in second faculty of Education at Tishreen University, And the instruments study were an achievement test , a performance test and an observational checklist. The training program was built as Models based self learning( The First was: Synchronous E-Voice Chatting and The Second was Asynchronous E-Voice Chatting). The results :There was significant statistical difference between the mean scores of students/ teachers in the pre- Achievement test and their means scores in the post- Achievement test in skills of E- voice chatting Synchronous and Asynchronous, There was significant statistical difference between the mean scores of students/ teachers in the pre- Performance test and their means scores in the post- Performance test in skills of E- voice chatting Synchronous and Asynchronous together and each one, There was significant statistical difference between males mean scores and females means scores in the post- Achievement test in skills of E- voice chatting Synchronous and Asynchronous in favour of females, There was no significant statistical difference between males mean scores and females means scores in the post- Performance test in skills of E- voice chatting Synchronous and Asynchronous. There was no significant statistical difference due to secondary certificate in the post- Achievement, and in the post- Performance test in skills of E- voice chatting Synchronous and Asynchronous.